The Development of Science Learning Devices with Guided Inquiry Model through Flipbook Media on Human Respiratory System Material to Train Critical Thinking Skills of Junior High School Students - Ilma, Indah Nafilatul; Susantini, Endang; Purnomo, Tarzan (International Journal for Educational and Vocational Studies, 2020)
This study aimed to produce a guided inquiry learning science model through flipbook media which is appropriate for training critical thinking skills for junior high school students on the Human Respiratory System material. The development of the device is a modification of the 4-D model which was tested on eighth grade students of the junior high school even semester semester 2019/2020 and was repeated twice. This is One-Group Pretest-Posttest Design research design and the data collection uses the method of validation, observation, tests, and questionnaires. The research data generated are validity, practicality, and effectiveness of learning devices analyzed descriptively quantitative and qualitative. The results showed that (a) learning devices developed were categorized as very valid, (b) learning activities were carried out very well with an average score of 3.69, (c) student activities in learning were carried out very well, (d) student responses to learning inquiry was very good (95.99%), and (e) the results of students' critical thinking tests had a high increase, critical thinking skills increased from 28.37 (Very Less Critical) to 81.21 (Critical). The conclusion of the science learning device with guided inquiry learning model through the developed flipbook media is appropriate to be used to train students' critical thinking skills.